Relationship Between Severe Preeclampsia, Gestational Hypertension, Impending Eclampsia, Preeclampsia, Superimposed Preeclampsia, and Chronic Hypertension on Fetal Outcomes at Respati Maternal and Child Hospital, Tasikmalaya - Utama, Firman Drajat; Desyari, Gina; Haruman, Kikeu Rizki; Perdana, Rikisetya Adhi (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: This study aims to explore the impact of preeclampsia on fetal outcomes at birth.Methods: This research used a total sampling method with a cross-sectional design. The data were from all pregnant patients and newborns delivered at Respati Maternity and Children’s Hospital, Tasikmalaya, in 2023. Hypertensive disorders included preeclampsia, severe preeclampsia (SPE), superimposed preeclampsia, gestational hypertension (GHT), impending eclampsia, and chronic hypertension, while fetal outcomes included birth weight and prematurity.Results: A total of 1,190 subjects were included. There was an association between birth weight and SPE (p < 0.01, PR = 7.64), GHT (p < 0.01, PR = 13.33), and superimposed preeclampsia (p < 0.05, PR = 5.24). A significant association was found between prematurity and SPE (p < 0.01, PR = 2.79), impending eclampsia (p < 0.05, PR = 3.63), superimposed preeclampsia (p < 0.01, PR = 4.47), and chronic hypertension (p < 0.05, PR = 3.63). No significant associations were found between other variables and low birth weight or prematurity.Conclusion: There is an association between SPE and superimposed preeclampsia with low birth weight and prematurity, between GHT and low birth weight, and between impending eclampsia and prematurity.Hubungan antara Preeklampsia Berat, Hipertensi Gestasional, Impending Eklampsia, Preeklampsia, Superimposed Preeklampsia, dan Hipertensi Kronis terhadap Luaran Janin di RSIA Respati TasikmalayaAbstrakTujuan: Penelitian ini bertujuan untuk mengeksplorasi lebih dalam mengenai dampak preeklampsia terhadap luaran bayi saat lahir.Metode: Penelitian ini dilaksanakan dengan metode total sampling, menggunakan desain potong lintang (cross-sectional) dengan data pasien ibu hamil dan janin yang dilahirkan di RSIA Respati Tasikmalaya pada tahun 2023. Variabel gangguan hipertensi meliputi preeklampsia, preeklampsia berat (PEB), superimposed preeklampsia, hipertensi gestasional (HTG), impending eklampsia, dan hipertensi kronis, sedangkan variabel luaran bayi meliputi berat badan lahir (BBL) dan prematuritas.Hasil: Sebanyak 1.190 subjek dikumpulkan. Terdapat hubungan yang signifikan antara BBL dengan PEB (p < 0,01, PR = 7,64), HTG (p < 0,01, PR = 13,33), dan superimposed preeklampsia (p < 0,05, PR = 5,24). Terdapat hubungan yang signifikan antara prematuritas dengan PEB (p < 0,01, PR = 2,79), impending eklampsia (p < 0,05, PR = 3,63), superimposed preeklampsia (p < 0,01, PR = 4,47), dan hipertensi kronis (p < 0,05, PR = 3,63). Tidak ditemukan hubungan antara variabel lainnya dan BBLR atau prematuritas.Kesimpulan: Terdapat hubungan antara PEB dan superimposed preeklampsia dengan berat badan lahir rendah dan prematuritas, terdapat hubungan antara HTG dan BBLR, dan terdapat hubungan antara impending eklampsia dan prematuritas.Kata kunci: Fetomaternal, Luaran Janin, Preeklampsia, RSIA Respati.